POTENSI PENGEMBANGAN DAYA TARIK WISATA ALAM BUWUN MAS GUNA MEWUJUDKAN PARIWISATA BERKELANJUTAN LOMBOK - Krismon Nusantara Saksi (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
The shift towards sustainable tourism aims to balance ecological preservation and local economic benefits. Buwun Mas Village in Lombok possesses immense natural potential, including pristine savannas and mangrove ecosystems. However, this potential is currently threatened by structural and institutional barriers. This study aims to evaluate the development potential of Buwun Mas's natural attractions and formulate a sustainable tourism management strategy. This research employed a qualitative approach with an intrinsic case study design. Data were systematically collected through in-depth interviews with key local stakeholders, moderate participant observation assessing the fundamental tourism components, and document analysis. The results indicate that, while the natural attractions are highly competitive, poor road accessibility and inadequate basic amenities severely limit tourists' length of stay and the resulting economic multiplier effects. Furthermore, the local Tourism Awareness Group faces significant institutional challenges, including a lack of independent financial capacity, limited digital marketing literacy, and a lack of strategic external partnerships. Consequently, the gap in strict local environmental regulations has led to physical degradation, such as savanna erosion caused by illegal off-road activities. In conclusion, transforming Buwun Mas into a sustainable tourism destination cannot rely solely on its natural beauty. It necessitates a collaborative intervention where the regional government must prioritise fundamental infrastructure development, while the village authority must immediately enact binding ecological conservation regulations to prevent future exploitation.